Profile of acute upper gastro intestinal bleed: a referral hospital-based study in sub Himalayan region - C. M., Shyamsundar; Sharma, Guru Dutt; Rana, Baldev Singh (International Journal of Advances in Medicine, 2018)
Background: Acute upper gastrointestinal bleeding (UGIB) is one of the most common medical emergencies and remains a major cause of morbidity and mortality. We are likely to see more of it in coming years with ageing population, patients with liver disease, increasing use of NSAIDs, single or multiple antithrombotic agents and novel anticoagulants, the present study was designed with the aim to assess the clinical profile of UGIB presenting to the Department of Medicine in sub Himalayan region. Methods: Study done over 12 months included all patients presenting with acute hematemesis and/or melena. Detailed history, clinical examination, blood tests and Upper GI Endoscopy was done in all patients. Results: One hundred seventy-five patients were included in the study, 129 (73.7%) were males. The commonest age group was 41-60 years contributing to 44%, male to female ratio 2.8:1. The commonest presentation was melena, patients with hematemesis presented earlier, with mean duration 1.46 days. 42.3% of patients were hemodynamically unstable at admission. The mean hemoglobin (Hb) was 8.224±2.78 g%. The cause of bleed was shared by ulcer, varices, non-ulcer non-variceal approximately 1/3rd each, major cause being ulcer in 39.4%. Varices was common in age 30-40 yrs, ulcer in age 51 to 70 years. Conclusions: UGI bleed was more frequent in males age between 41-60 yrs, peptic ulcer being the leading cause in our study, presence of signs of liver failure were associated with varices.